অসহযোগের দিনগুলি : মুক্তিযুদ্ধের প্রস্তুতিপর্ব - রহমান, আতিউর 1951-
Articles on the 1971 liberation movement of Bangladesh; chiefly on the non-cooperation movement called by Bangabandhu Sheikh Mujibur Rahman.